A critical review of environmental sustainability policies in light of Saudi Arabia’s Vision 2030 - Aldosari, Mubarak S (Research Journal in Advanced Humanities, 2026)
Environmental sustainability has moved from the margins of Saudi public administration to the centre of national strategy under Vision 2030. That shift is politically significant, but it is easier to publicise than to evaluate. This critical integrative review assesses how environmental sustainability has been framed, institutionalised, financed, and contested within the policy architecture associated with Vision 2030. It synthesises more than 100 sources, including official Saudi strategy documents, legal texts, climate submissions, multilateral reports, and interdisciplinary scholarship on environmental governance, water policy, climate politics, biodiversity, waste management, urban development, and sustainability transitions. The article argues that Vision 2030 has performed three substantial policy moves. It has made environmental sustainability highly visible within the national reform narrative; it has built a more differentiated institutional architecture through the National Environment Strategy, the 2020 Environmental Law, specialised environmental centres, and green-finance mechanisms; and it has linked environmental policy to economic diversification, quality of life, and international positioning. These are not trivial achievements. Yet visibility and institutional proliferation are not the same as ecological effectiveness. Across water, waste, conservation, climate governance, and mega-project development, the policy field still shows persistent tensions between ambition and implementation, centralisation and participation, target-setting and accountability, carbon management and hydrocarbon continuity, and environmental branding and independently verifiable outcomes. Saudi Arabia’s environmental turn is therefore best understood neither as empty rhetoric nor as settled transformation. It is an ambitious, state-led environmental transition whose long-term credibility will depend on whether legal authority, sectoral coordination, public data, and measurable ecological outcomes begin to align more closely than they do at present.